ChemInform Abstract: A New Method for Peptide Synthesis in the N→C Direction: Amide Assembly Through Silver‐Promoted Reaction of Thioamides. Issue 17 (April 2015) - Pourvali, Aysa; Cochrane, James R.; Hutton, Craig A.
Abstract N‐Protected amino acids (I) undergo an interesting Ag2CO3‐promoted coupling with amino ester thioamides to yield N‐acetylated dipeptides (III) without epimerization.